Enseignement professionnel et démarches d’investigation : le cas du Génie industriel textile - Valérie Théric; Hélène Cheneval-Armand; Alice Delserieys (Recherches en Éducation)
In a context of gradual evolution of the objectives of vocational teaching in France, inquiry based teaching strategies are more widely prescribed. This article focuses on the links between implicit prescriptions of inquiry based teaching and which activities are described by vocational teachers of industrial textile engineering. In particular, we want to identify if these declared activities fall into the description of pragmatic and/or explicative inquiry based teaching. Semi-structured interviews were conducted with six vocational teachers from different backgrounds and profiles. The interviews were conducted using a guide based on the characteristics of teacher's activity and inquiry based teaching. The analyses of these interviews have highlighted that, despite a certain lack of clarity in the prescriptions, interviewed teachers describe practices that fall into a pragmatic inquiry based teaching activity, and give a predominant place to practical activities.